2003
DOI: 10.1007/bf03327366
|View full text |Cite
|
Sign up to set email alerts
|

Association of health behavior and social role with total mortality among Japanese elders in Okinawa, Japan

Abstract: Our study results suggest that having sufficient hours of sleep and enhancing social role could greatly help elderly women in Okinawa to maintain good health. Moreover, our study provides direction for future research to explore the difference in adequate health promotion measures between women and men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 22 publications
1
36
0
Order By: Relevance
“…A total of 74 studies met the inclusion criteria; the process of study selection is shown in Figure 1 8, 9, 11, 12, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55, 56, 57, 58, 59, 60, 61, 62, 63, 64, 65, 66, 67, 68, 69, 70, 71, 72, 73, 74, 75, 76, 77, 78, 79, 80, 81, 82, 83, 84, 85, 86, 87, 88, 89,...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 74 studies met the inclusion criteria; the process of study selection is shown in Figure 1 8, 9, 11, 12, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55, 56, 57, 58, 59, 60, 61, 62, 63, 64, 65, 66, 67, 68, 69, 70, 71, 72, 73, 74, 75, 76, 77, 78, 79, 80, 81, 82, 83, 84, 85, 86, 87, 88, 89,...…”
Section: Resultsmentioning
confidence: 99%
“…** References 11, 21, 23, 25, 26, 27, 29, 32, 33, 34, 36, 39, 40, 41, 44, 46, 47, 48, 49, 51, 52, 53, 54, 56, 57, 61, 64, 66, 68, 70, 71, 72, 77, 79, 80, 84, 86, 87, 88.…”
Section: Notesmentioning
confidence: 99%
“…ECG ischemia, although associated with cardiovascular mortality in both sexes was not associated with all-cause mortality. In a Japanese study on elderly people, health behavior and social role were risk factors for all-cause mortality along with age, low serum albumin, high blood pressure and ECG abnormalities, among a total of 30 personal characteristics [4]. Other studies considered single or very specific risk factors for all-cause mortality such as the limited influence of soil-cadmium levels [2], the null influence of radar equipment [6], the direct role of respiratory symptoms [7], alcohol abuse [3], left bundle branch block [8], post-load plasma glucose [9], high basal metabolic rates [11], high body mass index [5,13], pessimistic side of the Minnesota Multiphasic Personality Inventory OptimismPessimism Scale scores [10], and high physical work demand [14].…”
Section: Discussionmentioning
confidence: 99%
“…Beyond the interest for cardiovascular diseases, this long observation prompted interest in allcause mortality and its determinants. A few studies have reported long-term analyses on all-cause deaths but rarely reaching 40-year of follow-up [1][2][3][4][5][6][7][8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…For the septuagenarian cohort, life expectancy from age 65 is the longest in Japan, and possibly the world, at 24.1 years for females and 18.5 years for males (Japan Ministry of Health, Labor and Welfare, 2005). Other factors may also be contributing to the exceptional longevity of the Okinawans such as genetic factors, specific nutritional components of the diet (high anti-oxidants), social support and/or health care (Takata et al 1987;Goto et al 2003;Todoriki et al 2004;Suzuki et al 2001Suzuki et al , 2004Willcox 2005;Willcox et al 2006). However, the forces of morbidity and mortality act most strongly at older ages and it is at these ages one would expect to see the most marked phenotypic differences and the most marked survival advantage, had CR occurred in the Okinawans, and indeed this is the case.…”
Section: The Okinawa Findingsmentioning
confidence: 99%